Relationship between Metisa plana and its parasitoids (braconidae and ichneumonidae) at different time-lags in oil palm plantation - Mohammad Hilmi Mohd Zahir,; Mohammad Zafrullah Salim,; Farrah Melissa Muharam,; Nur Azura Adam,; Dzolkifli Omar,; Nor Azura Husin,; Syed Mohd Faizal Syed Ali, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
Bagworm or Metisa plana, is the most important defoliator insect in the oil palm cultivation, while parasitoids such as Braconidae and Ichneumonidae are the common main natural enemies for bagworm. Although the relationship between natural enemies with its insect pest has been broadly investigated, little is dedicated for assessing the delayed effects of the bagworm population on parasitoids. In this study, the abundance relationship between bagworm and its common parasitoids (Braconidae and Ichneumonidae) was assessed at different time-lags under field condition. Bagworm censuses for instar stages first (L1) to seven (L7) were conducted biweekly in an oil palm plantation belongs to TH Plantation Berhad in Muadzam Shah, Pahang from July 2016 to July 2017, along with bagworm’s parasitoid from Braconidae and Ichneumonidae family. The results revealed that Braconidae presence was associated positively with bagworm at week 6 to 12, whereby the associations were stronger for late instar stages. On the other hand, Ichneumonidae presence was positively related to middle instar stages at early time-lag i.e. week 2 to 6. In other words, Ichneumonidae population is expected to increase after 2 to 6 weeks given increasing population of bagworm, while Braconidae population is likely to rise after 6 to 12 weeks of the increasing population of bagworm.